ANALISIS SIFAT KIMIA TANAH PADA TANAH YANG DI TANAMI TANAMAN TOMAT(Solanum Iycopersicum L)DI DESA TONSEWER MINAHASA ANALYSIS OF SOIL CHEMICAL PROPERTIES ON SOILS THAT ARE TOMATOUS PLANTS (Solanum Iycopersicum L) IN TONSEWER MINAHASA VILLAGE - Steven Tambanaung; Diane D, Pioh; Wiesje J. N. Kumolontang (Universitas Sam Ratulangi, 2018)
ABSTRACT SoilÂ is a natural body that occupies most of the surface of planet Earth.Â Soil as a medium for growing plants with various properties possessed. Tomato cultivation is not only on plantation land.Â Soil chemistry concerns the composition of minerals, organic matter, and environmental factors. Components of soil chemistry include pH, organic C and essential nutrients. Soil reaction (pH) is a characteristic or parameter that shows acidic conditions in the soil. The taste of tomatoes is sweet - fresh sweetness that can provide freshness to the body. The optimal rainfall for tomato growth is 100-220 mm / rain with the ideal daily temperature, which is 25-30oC. Keywords: Soil Chemical Properties, Tomato Plants